Surface Characteristics of Azospirillum brasilense in Relation to Cell Aggregation and Attachment to Plant Roots - Burdman, Saul; Okon, Yaacov; Jurkevitch, Edouard (Critical reviews in microbiology, 2000)
The free-living bacteria of the genus Azospirillum live in close association with plant roots and represent one of the best-characterized plant growth promoting rhizobacteria (PGPR). The attachment of Azospirillum to the roots is essential for the establishment of an efficient association with the host plant. Azospirillum cells are able to aggregate under certain environmental conditions, leading to the formation of bacterial flocs. The bacterial surface plays an important role in the establishment of the bacteria-plant association as well as in the bacterial aggregation and data suggesting the involvement of extracellular polysaccharides and proteins in these phenomena have been published. This review summarizes the current knowledge on the involvement of surface components in the adhesion processes of Azospirillum. Emphasis is placed on A. brasilense, the species that has been the subject of most studies in the Azospirillum genus.